Kemitraan Tebu Rakyat Dan Dampaknya Terhadap Kinerja Usahatani Tebu Di Kabupaten Lampung Utara (Jurnal Agribisnis Indonesia, 2025)
This study aims to analyze the factors that influence farmers' decisions to join partnerships and their impact on the performance of smallholder sugarcane farming businesses. The survey was conducted from December 2023 to March 2024. The sample in this study amounted to 189 respondents consisting of 96 partner farmers and 93 non-partner farmers. The research method involved descriptive analysis and Propensity Score Matching (PSM) to compare the performance of partner and non-partner farmers. The results showed that the factors that influenced farmers to join partnerships included age, education, number of family members, distance from partner locations, distance from factory locations, and attitude towards risk, while land area, farming experience, and frequency of extension had no significant effect. Based on the Propensity Score Matching (PSM) analysis, partnerships significantly increased income, production costs, transaction costs, and productivity, but had no significant effect on the selling price of sugarcane. Although partnerships increase productivity, income, and cost efficiency of farming businesses, several obstacles are still faced, such as limited market information, non-transparent determination of yields, and additional costs due to queues at the factory. The results of this study are expected to be input for the development of sugarcane agribusiness policies in Indonesia.